Induction of mitochondrial-mediated apoptosis in HT-29 human colorectal adenocarcinoma cells by aqueous fraction of Nephelium ramboutan-ake rind. / Chan Chim Kei - Chan, Chim Kei (2013)
The objective of this study was to evaluate the cytotoxic effect and elucidate the possible underlying apoptotic mechanisms of Nephelium ramboutan-ake (pulasan) rind in selected human cancer cell lines. The crude ethanol extract and fractions (ethyl acetate and aqueous) of N. ramboutan-ake reduced the cell viability of HT-29, HCT-116, MDA-MB-231, Ca Ski cells by MTT assay. The N. ramboutan-ake aqueous fraction (NRAF) was found to exert the most potent cytotoxic effect against HT-29 cells in a dose-dependent manner. Further investigation for its plausible mechanisms was conducted by using flow cytometry and fluorescence microscopy. This study confirmed the induction of apoptosis by a series of archetypal apoptotic features such as chromatin condensation, DNA fragmentation, cell shrinkage and apoptotic body formation by Hoechst 33342/PI dual staining. The apoptotic mechanisms were further substantiated with the detection of DNA fragmentation by TUNEL assay and phosphatidylserine (PS) externalization on the outer leaflet of plasma membrane which detected by annexin V-FITC/PI binding confirming the early stage of apoptosis. In addition, mitochondrial permeability transition is a vital step in the induction of cellular apoptosis, and data clearly revealed that NRAF resulted in disruption of mitochondrial transmembrane potential (Δψm) in HT-29 cells. Dissipation of Δψm was indicated through a series of evidences such as increased generation of ROS and depletion of GSH, upregulation of Bax protein expression, as well as activation of caspase-3/7 and caspase-9. Collectively, these results suggested that NRAF induced mitochondrial-mediated apoptosis.